Performance analysis of atmospheric optical communication systems with spatial diversity affected by correlated turbulence - Álvarez-Roa, María; Álvarez-Roa, Carmen; Fernández-Aragón, F.; Raddo, Thiago; Garrido-Balsells, José María; Tafur-Monroy, I.; Jurado-Navas, Antonio (Optica Publishing Group / IEEE, 2022)
This paper presents a complete analytical framework for obtaining the performance associated with a free-space optical (FSO) communication system with a spatial diversity and equal gain-combining technique. The system is affected by gamma–gamma scintillations with different realistic degrees of channel correlation depending only on the physical parameters of the link. We derive new analytical closed-form expressions for the average bit error rate (ABER) considering different scenarios to provide very realistic behavior of the system including different numbers of FSO receivers in several geometric configurations, with different receiving areas, different path lengths, and a variety of turbulence conditions. Furthermore, a very accurate approximate closed-form expression is also derived for the ABER of any generic coding scheme with either a very complex or, directly, no closed-form expression for its associated conditional BER that is first obtained in the ideal case of absence of turbulence. Numerical results via Monte Carlo simulation are provided to corroborate the validity of all the derived analytical expressions.
https://openpolicyfinder.jisc.ac.uk/id/publication/29757?from=single_hit
Keywords: Sistemas de comunicación inalámbricos; Turbulencia atmosférica; Wireless optical communications; Correlation; Atmospheric turbulence